Use of extracorporeal blood purification therapy (ECBPT) as an adjuvant to high-dose corticosteroids in a severely ill COVID-19 patient with concomitant bacterial infection - Min Xian Lim; Kean Khang Fong; Yeap, Boon Tat (BMJ Publishing Group, 2021)
COVID-19 presents with a spectrum of severity, ranging from asymptomatic or mild symptoms to those with acute respiratory distress syndrome. Corticosteroids are widely used for their efficacy in reducing inflammatory responses. However, its use may be limited to patients with immunosuppression. An adjunct therapy for cytokine storm in COVID- 19 is extracorporeal blood purification therapies using high adsorptive filters, such as oXiris, to remove cytokines. We share our experience in using continuous renal replacement therapy with oXiris haemofilter as a temporising measure to high- dose corticosteroids in managing cytokine storm in a deteriorating COVID- 19 patient with concomitant bacterial infection.